Are Currently Used Bioimpedance Methods in Hemodialysis Comparable for Calculating Dialysis Dose?. Issue 2 (20th November 2019) - Arias‐Guillén, Marta; Masso, Elisabet; Gomez, Miquel; Rodas, Lida; Broseta, Jose; Vera, Manel; Rios, Jose; Fontseré, Néstor; Maduell, Francisco
Abstract: Bioelectrical impedance analysis has increasingly been incorporated into hemodialysis units (HD) as a useful, noninvasive technique for evaluating overall fluid status. The aims of this study were to verify whether the information obtained from two different bioelectrical impedance analysis methods (spectroscopy bioimpedance [BCM] and single‐frequency bioelectric impedance vector analysis [SF‐BIVA]) was comparable for analyzing fluid status, and to determine their impact when used to calculate dialysis dose. This observational cross‐sectional study included 78 HD patients who underwent one measurement with BCM and one with SF‐BIVA in the same dialysis session. For calculating the dialysis dose, total body water or urea distribution volume ( V ) was calculated by the Watson formula and compared with the V obtained from the two devices. The difference in V between the two devices was 5.4 L ( P < 0.001). Given the existent correlation between V BCM and V SF‐BIVA, we were able to apply a formula (corrected V = V SF‐BIVA = 1.04 × V BCM + 4.85, r = 0.93), allowing comparison of the two bioimpedance methods. The mean dialysis dose for BCM device (KtID / V BCM ) was 2.49 ± 0.85, much higher than KtID / V SF‐BIVA (2.06 ± 0.72) mainly due to the V obtained with the different devices, with KtID / V Watson being 2.03 ± 0.67. The results on volume distribution showed an acceptable correlation but the devices were not comparable due to intermethod differences observed. Dialysis centers using SF‐BIVA will obtain much lower dialysis dose, but by applying our formula, the Kt/ V would resemble that obtained by the BCM device.